2006
DOI: 10.1136/bmj.38683.710255.be
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcomes from the IMPACT randomised trial for depressed elderly patients in primary care

Abstract: Objective To determine the long term effectiveness of collaborative care management for depression in late life. Design Two arm, randomised, clinical trial; intervention one year and follow-up two years. Setting 18 primary care clinics in eight US healthcare organisations. Patients 1801 primary care patients aged 60 and older with major depression, dysthymia, or both. Intervention Patients were randomly assigned to a 12 month collaborative care intervention (IMPACT) or usual care for depression. Teams includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
210
0
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 301 publications
(221 citation statements)
references
References 21 publications
6
210
0
5
Order By: Relevance
“…Importantly, it confirms in a general adult population previous findings from earlier studies employing at least three PCMH characteristics, of significant reductions in ED visits among high-risk elderly randomized to home-based, interdisciplinary care including PCP, specialty care, and a care manager; 9,10 significant increases in quality of both processes and outcomes of care among depressed elderly randomized to collaborative care including care management, PCP and a specialist; 11 and trends in ED cost reductions seen among older patients at high risk of heavy use of health care services randomized to PCP-led team care with care management. 6 It also increases confidence in reports of positive outcomes from demonstrations with design and evaluation limitations.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Importantly, it confirms in a general adult population previous findings from earlier studies employing at least three PCMH characteristics, of significant reductions in ED visits among high-risk elderly randomized to home-based, interdisciplinary care including PCP, specialty care, and a care manager; 9,10 significant increases in quality of both processes and outcomes of care among depressed elderly randomized to collaborative care including care management, PCP and a specialist; 11 and trends in ED cost reductions seen among older patients at high risk of heavy use of health care services randomized to PCP-led team care with care management. 6 It also increases confidence in reports of positive outcomes from demonstrations with design and evaluation limitations.…”
Section: Discussionsupporting
confidence: 73%
“…Only one reported reductions in emergency department visits (ED), 9,10 and one reported suggestive but inconclusive reductions in ED visits. 6 Two studies reported significant improvements in quality of care processes 11 and/or outcomes. 9,11 These studies, 3 with their adequate power, design and evaluation rigor, focus on older, 6,9-12 low income, 10 high risk, 6 and unique populations such as homebound Veterans, 5 and therefore lack generalizability to the vast majority of primary care practices in the U.S. that may be considering or attempting the PCMH transition.…”
Section: Introductionmentioning
confidence: 99%
“…In the disease management approaches that have been extensively evaluated in the United States, this usually implies interaction between a depression case manager and psychiatrist, 37 but in Canada, the emphasis has been on shared care between a primary care professional and mental health care specialists. Shared care often involves placement of mental health professionals in primary care practices, but, unlike chronic disease management strategies, the shared care philosophy conveys no definite implications for activities such as screening or guided self-management.…”
Section: Implications For Depression Researchmentioning
confidence: 99%
“…Results indicated that participants reported improvements in depressive symptoms, overall functioning, and adherence to recommended exercise 26,28 and that many of these gains were maintained even after the intervention was discontinued. 29 The intervention did not result in improved glycemic control, although this finding may have resulted from the limited hemoglobin A 1c range in the study sample.…”
mentioning
confidence: 83%